POLA PERTUMBUHAN IKAN SELAR (Selaroides Leptolepis) DI PERAIRAN KABUPATEN MALUKU TENGGARA - Eka Anto Supeni; Erna Almohdar (Fish Scientiae, 2017)
Fish selar (Selaroides leptolepis) is one type of fish consumption that has high economic value and many caught in Southeast Maluku district waters. As an important resources, information on various aspects of fish biology is needed in order to support its management efforts. Therefore, this research is aimed to see the pattern of fish growth in Southeast Maluku waters. This research was conducted using data of catch in Sathean and Selayar village of southeast Maluku district collected during March until July 2017. The total samples of fish selar used were 877 individuals with total length size 100 t0 247 mm and means length 161.64 ± 0.82 mm and weight size 8.80 to 165.70 gram with means weight 46.39 ± 0.86 gram. The result of analysis between length and weight selar fish equation W = 0.0000008L3.044, with the growth pattern of selar fish in Southeast Maluku waters is isometric.